Pelatihan Penyusunan Bahan Ajar Berbasis Pendekatan Deep Learning Bagi Guru Matematika di Kabupaten Lumajang - Yayan Eryk Setiawan; Khoirul Muttaqin; Triwilujeng Ayuningtyas (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to improve teachers’ understanding and skills in developing instructional materials based on the deep learning approach. The program was implemented through training and mentoring activities involving 35 mathematics teachers. Evaluation instruments consisted of two questionnaires: a 17-item questionnaire measuring teachers’ understanding of the deep learning approach and a 14-item questionnaire assessing teachers’ skills in developing deep learning–based instructional materials. The questionnaire data were analyzed descriptively. The results indicate that the teachers’ average level of understanding of the deep learning approach reached 83.63%, while their skills in developing instructional materials reached 82.62%, both of which fall into the very good category. These findings imply that the program effectively enhanced teachers’ understanding and skills in designing deep learning–based instructional materials and supports government efforts to implement deep learning–oriented instruction.